1996
DOI: 10.1111/j.1365-2044.1996.tb07883.x
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of serial measurements of serum albumin concentration in patients admitted to an intensive care unit

Abstract: SummaryThe Hypoalbuminaemia is associated with increased hospital morbidity and mortality [I] and has been shown to be a reliable prognostic indicator. Although serum albumin concentration was included in the APACHE Ill (Acute Physiology And Chronic Health Evaluation) illness severity scoring system [2], it is not a component of the more widely used APACHE I1 [3]. It is known that the accuracy of outcome prediction of APACHE I1 is impaired in patients with severe hypoalbuminaemia, which is itself an independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
2
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 15 publications
3
31
2
1
Order By: Relevance
“…This study also shows that leukocytosis is associated with thrombocytosis, a known negative prognostic indicator in patients with cancer [21,22]. In this cohort baseline leukocytosis correlates with several clinical findings known to be associated with underlying inflammation including thrombocytosis [23], hyperglycemia [24,25], hypoalbuminemia [26,27], and transaminitis [28,29]. …”
Section: Discussionmentioning
confidence: 55%
“…This study also shows that leukocytosis is associated with thrombocytosis, a known negative prognostic indicator in patients with cancer [21,22]. In this cohort baseline leukocytosis correlates with several clinical findings known to be associated with underlying inflammation including thrombocytosis [23], hyperglycemia [24,25], hypoalbuminemia [26,27], and transaminitis [28,29]. …”
Section: Discussionmentioning
confidence: 55%
“…Reduced serum albumin concentration correlates with the increased mortality of critically ill patients 25,26. Previously, it has been shown that the BChE activity correlates with the albumin concentration in critically ill patients with severe systemic inflammation 7.…”
Section: Discussionmentioning
confidence: 98%
“…One study that comprised Swedish elderly patients with community-acquired pneumonia [33] and two studies including intensive care unit patients [34,35] supported our view that hypoalbuminaemia mainly reflected an acute inflammatory response. Our results are in line with results reported in those studies.…”
Section: Discussionmentioning
confidence: 91%